Does Nailing Distal Tibia Metaphyseal Fracture with Modified Interlocking Nail Produce Acceptable Outcome? (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the functional results of distal tibia metaphyseal fractures treated with modified (shortened) interlocking nail and K wire fixation of the fibula.Methods: This descriptive study was conducted in Trimax Hospital Karachi from 20th June 2017 to 20th June 2020. All adults patients with distal tibia (5cm) and fibula (?10cm) meeting the inclusion criteria were operated with modified (distal one centimeter of the standard nail was cut) interlocking nail in the tibia and K wire in the fibula. Functional results were assessed at 6th month with the American Orthopaedic Foot & Ankle Society (AOFAS) questionnaire score and graded as excellent, good, fair and poor. Comparison of AOFAS scores in both gender, sides and fracture types was done and P value was calculated for statistical significance. P < 0.05 was considered significant.Results: The total number of patients in our study were 60. The mean age of our patients was 33±11.5 years. Male patients were 51(85%) and female 9(15%).Right tibia fibula was fractured in 49(81.6%) and left in 11(18.3%). The average union time was 15±4 weeks (range 13 to 18 weeks) As per AOFAS questionnaire score 36(60%) patients had excellent outcome,13 (21.6%)  good and 11(18.3%) had fair outcome. No significant difference was found in AOFAS scores with regard to gender, sides and type of fractures (P>0.05).Conclusion: Majority of the patients treated with modified (shortened) interlocking nail tibia and K wire fixation fibula achieved excellent and good functional outcome. We therefore recommend this treatment protocol for all patients with distal tibia and fibula fractures.